THE EFFECT OF VARIATIONS IN THE COMPOSITION OF CANDLENUT SHELLS AND BAGASSE ON THE CHARACTERISTICS OF BRIQUETTES - Ayudhia Gina Mawaddha; Mietra Anggara (Mechanical, Energy and Material (METAL), 2023)
Currently, the world is facing a critical energy shortage. Every year, there is an increasing number of human activities that require fuel, especially oil-based fuels. Briquettes are one of the alternative energy sources that can be used to replace some of the uses of kerosene. The biomass used in this research consists of candlenut shells, sugarcane bagasse, and tapioca flour as a binder. The aim of this research is to determine the influence of briquette composition on the characteristic values of the briquettes. The tests conducted in this research include: calorific value, moisture content, ash content, volatile matter content, and fixed carbon content. The research results show that the highest calorific value in this study is found in sample 4, with a composition of 90% candlenut shells and 10% binder, with a calorific value of 5329 cal/g. For the composition of 30% sugarcane bagasse and 60% candlenut shells, the moisture content is 6.26%. The ash content is 1.23% for the composition of 30% sugarcane bagasse and 60% candlenut shells. The volatile matter content is 28.22% for the composition of 90% candlenut shells and 10% binder. Lastly, the fixed carbon content is 28.22% for the composition of 60% sugarcane bagasse and 30% candlenut shells.